Immune-mediated skin diseases and erectile dysfunction: mechanisms and multidisciplinary management - Lv, Chengsen; Cao, Hongliang; Zhao, Dingliang; Yang, Yongjin; Ma, Zhen; Zhang, Yinuo; Wu, Xingyu; Chen, Mo; Gao, Jialin (Frontiers in Immunology, 2026)
The global prevalence of erectile dysfunction (ED) continues to rise, which has become an important issue affecting the physical and mental health of men. Existing evidence suggests that ED is closely related to various immune-mediated skin diseases. This review elaborates on the epidemiological characteristics, potential mechanisms, and clinical management strategies of ED associated with immune-mediated skin diseases. It discusses the future research directions and challenges in this field. Epidemiological studies consistently show that the prevalence of ED in such patients is higher than that in the general population, indicating that immune-mediated skin diseases may significantly increase the risk of ED. Its pathogenesis is complex and diverse, involving the interaction of multiple pathways. In terms of clinical management, a multidisciplinary collaborative model is advocated, with the active control of the inflammatory activity of the primary skin disease as the cornerstone of treatment. The treatment of ED should be individualized, combined with psychological intervention and lifestyle optimization, to comprehensively improve the treatment effect. Future research should further explore its molecular mechanisms and conduct large-sample, prospective clinical trials to optimize treatment strategies and ultimately enhance patients’ sexual health and overall quality of life (QoL).